Feral Atlas (Stanford University Press, 2020)
Every event in human history has been a more-than-human event. When hunter-gatherers burn the land, they cooperate with herbs that seed quickly and grasses that sprout after fires, attracting game. Inside us, intestinal bacteria make it possible for us to digest our food. Other things, living and nonliving, make it possible to be human. Yet powerful habits of thought over the last centuries have made this statement less than obvious. With the arrival of the idea of the Anthropocene, we move away from such thinking to reconsider how human and nonhuman histories are inextricably intertwined. Convening over one hundred researchers to trace a whole range of such intertwinements, Feral Atlas offers an original and playful approach to studying the Anthropocene. Focused on the world's feral reactions to human intervention, the editors explore the structures and qualities that lie at the heart of the feral and make the phenomenon possible. This publication features original contributions by high-profile artists, humanists and scientists such as Amitav Ghosh, Elizabeth Fenn, Simon Lewis, Mark Maslin, and many others.